[Empire Marketing Board posters] - Großbritannien Marketing Board; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 2007)
A collection of 41 posters from the National Archives depicting trade and industry advertisements from Australasia, South Asia, Africa, Middle East and Canada. Includes collective portraits of prominent figures such as Sir Francis Drake, Sir Walter Raleigh, James Cook, T.E. Lawrence, General Gordon, Dr. Livingstone, Cecil Rhodes